2015
DOI: 10.2139/ssrn.2585324
|View full text |Cite
|
Sign up to set email alerts
|

Game, Set, and Match: Do Women and Men Perform Differently in Competitive Situations?

Abstract: This paper analyzes potential gender differences in competitive environments using a sample of over 100,000 professional tennis matches. Focusing on two phenomena of the labor and sports economics literature, we find robust evidence for (i) the hot-hand effect (an additional win in the most recent ten matches raises the likelihood of winning by 3.1 to 3.3 percent) and (ii) the clutch-player effect, as top players are excelling in Grand Slam tournaments, the most important events. Overall, we find virtually no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…Second, men and women exhibit virtually identical results, suggesting that competitive women can tackle failures just as well as competitive men. The result is in line with results from observational studies on professional tennis players (see Wozniak, ; Jetter and Walker, ; Banko, Leeds, and Leeds, ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Second, men and women exhibit virtually identical results, suggesting that competitive women can tackle failures just as well as competitive men. The result is in line with results from observational studies on professional tennis players (see Wozniak, ; Jetter and Walker, ; Banko, Leeds, and Leeds, ).…”
Section: Resultssupporting
confidence: 90%
“…Wozniak () and Jetter and Walker () both use data from all‐male and all‐female professional tennis tournaments to study how the probability of winning the current game is affected by previous results. They both find that men and women are more likely to win the current game if they have experienced recent successes, and they also see that these effects are very similar in magnitude across the genders.…”
mentioning
confidence: 99%
“…This finding is in strict opposition to anecdotal and common sense evidence presented in the media by journalists, coaches, and players. Wozniak (2012) and Jetter and Walker (2015) focused on the "hot-hand effect," analysing any differences between women and men in influences of the previous matches on their competitive performance. Wozniak (2012) revealed gender differences and similarities: "[B]oth men and women are more likely to enter tournaments after doing well, but women are affected by their last tournament while men's previous performance can affect entry beyond the next tournament" (p. 158).…”
Section: Studies Analysing the Differences In Female And Male Tennis Players' Performancementioning
confidence: 99%
“…The higher ability women also react positively to the results from their last tournament while men do not (Wozniak, 2012). Jetter and Walker (2015) found, in their examination of the hot-hand effect, no gender differences at all, then went further to analyse the "clutch-player effect" and found that "top-ranked female players are at least as likely as males to perform well in important matches." (p. 107) Contrary to those results, the most recent study of De Paola and Scoppa (2017) had the following findings:…”
Section: Studies Analysing the Differences In Female And Male Tennis Players' Performancementioning
confidence: 99%
“… Recent studies have exploited the fact that tennis is one of the few sports where men and women earn comparable amounts of compensation, yet compete in separated events (e.g., see Jetter and Walker, , studying hot hand and clutch player effects, or Grove and Jetter, , who analyze the progression from juniors to professional tennis players). Golf may be the only other exception.…”
mentioning
confidence: 99%